KAJIAN TERHADAP PELAKSANAAN PROGRAM CHSE DI LOKASI WISATA BUMI KEDATON BANDAR LAMPUNG SERTA IMPLIKASI DAN KEBERLANJUTAN PASCAPROGRAM - Nurnastiti, Salma Hanifah; Tresiana, Novita; Karmilasari, Vina (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
This study aims to evaluate the implementation of the CHSE program at the Bumi Kedaton tourist site in Bandar Lampung City, based on William N. Dunn’s policy evaluation indicators. The research employs a qualitative descriptive approach with data collection techniques including interviews, documentation, observation, and literature review. Informants were selected using purposive sampling with criteria directly related to the subject of the study. The findings reveal that the program was fairly effective in increasing the awareness of managers regarding the importance of cleanliness and safety during the pandemic; however, its implementation declined after certification. In terms of efficiency, the use of resources such as labor and time was optimal during the program, but limited funding hindered its sustainability. Regarding adequacy, the program provided sufficient support during the pandemic but did not fully meet the long-term needs of the managers due to the absence of continued assistance or encouragement from the government. In terms of equity, socialization efforts reached all stakeholders evenly, but implementation decreased and became less consistent after the pandemic subsided. The program was responsive to urgent needs during the pandemic but failed to address the managers’ needs in maintaining post-pandemic standards due to a lack of updated strategies. Although the program's targets were appropriate, it lacked strategic planning to ensure ongoing implementation beyond the pandemic period.